V. Solovyov’s Views on Chinese Religions - CHAI, Xudong (Journal of Research for Christianity in China (JRCC), 2025)
Religions of the Eastern world constituted a sustained intellectual preoccupation for Solovyov and served as a critical frame of reference in his conceptualization of Russian national character and the nature of religion itself. In his discussions, ancient Chinese philosophy, mystical religions, and the crucial principle of patriarchy together constitute the religious beliefs of the Chinese people, while such a religion also hinders China’s progress toward absolute values. His philosophical system was fundamentally shaped by the dialectical opposition between Slavic and Western traditions, as well as between Eastern Orthodox and Western Christian traditions, with the ultimate teleological aim of establishing a universal Christian church and achieving collective human salvation. His perspective on China is an organic component of his moral philosophy and his theocratic teachings, and thus an essential element for understanding the Christian world’s perception of China.